Pengaruh Penetapan Harga Jual Produk Thrifting Terhadap Minat Beli - Arizal Hamizar; Rosalinda Nadam Buton; Darwis Amin (Journal of Business Application, 2025)
This study aims to determine the effect of product thrifting price determination on consumer purchase intention. The research employs a quantitative approach with data collection techniques using questionnaires and documentation. The sample of the study consisted of 71 respondents. Data analysis methods include instrument testing (quantitative descriptive test), descriptive percentage analysis, classical assumption tests, and hypothesis testing with the assistance of SPSS 20. The results indicate that the selling price of thrifting products significantly influences consumer purchase intention at Pasar Lorong Tahu Ambon, with an Adjusted R-Square value of 55.4%. This means that more than half of the variation in consumer purchase intention can be explained by pricing factors. From a managerial perspective, price indicators such as price affordability, price-quality conformity, price comparison with similar products, and price transparency were proven to affect consumer decisions to buy. These findings emphasize that an appropriate pricing strategy in thrifting businesses such as maintaining competitive prices, adjusting prices to product quality, and ensuring price transparency can increase consumer interest and purchase intention. Meanwhile, the remaining 44.6% of the variation is influenced by other factors outside this research, such as promotion, fashion trends, and individual preferences.